Enseñanza y aprendizaje de la modelización - Martinand, J.L. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
A general outline of a research program on the teaching/learning of modelization, being carried out at the moment, is presented. Particular reference is made to the difficulties of learning modelization considering the different types of activities, rhythm, etc. which are suitable to help such learning. As an instance, both relationships force -energy and the atomic model were chosen.